A proteção do meio ambiente como um dos direitos fundamentais da constituição da República Federativa do Brasil de 1988 e o problema da legitimidade e da representação adequada para a sua concretização pelo processo - Beltrão, Antônio Figueiredo Guerra (2010)
This essay assesses, from the comunitarianism doctrine perspective, the environmental protection as a fundamental right on the Brazilian Constitution of 1988 and the environmental class actions adequacy of representation and standing to sue. The paper comprehends 4 (four) chapters. The first one deals with the communitarian doctrine, which, by its emphasis on unity of a project for the whole society, may represent the fundament for a new paradigm of law, grounded on the collective rights primacy, representing the antithesis of liberalism individualistic thought. The second chapter analyses the right to environment as a fundamental right on the Brazilian Constitution of 1988, and therefore its implementation with the utmost efficiency and effectiveness in the process, affecting the burden of proof. The third chapter includes a brief exam of the class actions in Brazil, an instrument to fulfill the basic right to the environment, and its relation to individual lawsuits, from the analysis of connection, continence, lis pendens and res judicata. Finally, the fourth chapter assesses the impropriety of the proceeding established by the Federal Act nº 4.717/1965 for the environmental citizen lawsuits as well as investigates the issue of standing to sue and adequacy of representation on environmental class actions, including the possibility of its individual initiative. The method employed in this essay consists in examining the Brazilian legislation and its interpretation given by the superior courts and the doctrine. All precedents assessed are from the Supreme Court or the Superior Court of Justice, as the authentic interpreters of the Constitution and Brazilian laws, respectively. The quotations throughout the paper apply the general method, indicating the author, title, location, publisher, year and page